From the Editor: The Next Generation. (1st June 2022) - Kelly, Rob
Abstract : Sorry, Star Trek fans, the TV series is not the topic of interest here. Instead, the starting of the fourth decade of Interface calls for not only looking back, but also looking forward. I looked back in the Spring 2022 editorial, with a sneak peek of the future of an all-digital Interface. I am happy to note that the print-on-demand option has already been a big hit for those with the continued desire for a tactile reading experience, not to mention the best-looking covers for displays on coffee tables worldwide. Now is the time to look forward and start involving the next generation of members across all the activities of the Society.